HUBUNGAN KETERAMPILAN MEMBACA KRITIS DENGAN KETERAMPILAN MENULIS KARANGAN ARGUMENTASI SISWA KELAS XI SMA NEGERI 2 PULAU PUNJUNG KABUPATEN DHRMASRAYA - Yetri, Elva; Ratna, Ellya; Helda, Trisna (Pendidikan Bahasa Indonesia, 2014)
This research is motivated by three things. First, the lack of students reading skills . Second, students had difficulty finding the main idea in a reading, because students are less earnest in reading. Third, students are not able to make an argument writing effectively and efficiently. This study aims to describe the relationship of critical reading skills with essay writing skills argumetasi class XI student of SMA 2 Island Dharmasraya Arbor. This study was collected on December 29 and January 30, 2013. Quantitative type of research is descriptive method . The study population was a class XI student, amounting to 133 spread over four classes. This research instrument is an objective test for critical reading and performance tests to write the essay s argument. Based on the data analysis and discussion , it was concluded three things. First, critical reading skills is more than enough that is classified as 75.12 %. Second, the argument essay writing skills that students classified as either 83.08 %. Third, there is a significant relationship between critical reading skills with the skills of writing essays arguing with n - 1 degrees of freedom and a significant level of 95 % ( 3.5154 ). Based on these conclusions, Ho is rejected and H1 is accepted for the results of the test prove that t_ ( count ) is smaller than Â t_tabel ie, 3.5154 > 1.70